Answer:
A) x = (-8log(6)-2log(17))/(-2log(17)+log(6))
Step-by-step explanation:
Taking the logarithm of the equation, you have ...
(x+8)log(6) = (2x-2)log(17)
Subtracting the right side from the equation gives ...
x(log(6) -2log(17)) +8log(6)+2log(17) = 0
Subtracting the constant and dividing by the coefficient of x gives ...
x = -(8log(6) +2log(17))/(log(6) -2log(17)) . . . . . matches selection A
___
You don't need to work out the whole solution to determine the correct answer choice. Once you take the initial log, you find that the x-coefficient includes a multiplier of 2log(17). This term only appears in the denominator of choice A. (The value of x will be found after dividing by the x-coefficient, so you know this must show up in the denominator of the answer.)
Answer:
tigers
Step-by-step explanation:
Solution:
f(x) = 2x + 3
g(x) = x - 9
f(x) + g(x)
= (2x + 3) + (x - 9)
= 2x + x + 3 - 9
= 3x - 6
Answer:
a(n) = -20 + 3(n - 1)
Step-by-step explanation:
a(n) = -20 + 3(n - 1)